Students during the first six weeks of the 1935-36 Spring quarter. - Unknown:::Creator::::::::::::
Written on verso:"Spring Quarter 1935-1936; 1st 6 weeks Wilma Gottburg, Winifred Fagau, Dorothy Bergquist, Ruth Graves."